Pengembangan Essay Assessment pada Proses Pembelajaran Dasar Listrik dan Elekronika - Iqbal Nurhuda; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2021)
Vocational high school requires students to be competent in every learning that is carried out, according to the curriculum 2013 which has characteristics in mastering concepts as a whole and hones the abilities of students. The fact that happens is that the learning process of basic electricity and electronics that is carried out has not been able to improve the competence of students. The results of the analysis of the characteristics of students showed that there were still many students who were not competent in learning. This study aims to produce a valid, practical, and effective assessment essay that can improve students' competence in basic electrical and electronics competencies. This type of research is a research and development (research and development) using a 4-d model which consists of the stages of define (define), design (design), develop (development), and disseminate (spread). The research instrument was validated first by five validators before being used to collect data. the data collected in this study include data validity, practicality, and effectiveness. The data analysis technique used is a descriptive analysis which is presented in graphic form. the results showed that the assessment essay based on the creative problem-solving model developed was very valid), to increase the competence of students, as seen from the knowledge competency, attitude competence, and skills competency in basic electrical and electronics learning.